Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1093/humrep/del114
|View full text |Cite
|
Sign up to set email alerts
|

Protamine 2 precursors, protamine 1/protamine 2 ratio, DNA integrity and other sperm parameters in infertile patients

Abstract: The levels of pre-P2 may provide clues into the pathogenic mechanisms of infertility. The increased proportion of pre-P2 in some patients with increased P1/P2 ratio suggests an involvement of pre-P2 processing. The positive correlation between TUNEL-positive sperm and pre-P2 at low pre-P2/P2 ratios also suggests a link between deficient protamine processing and decreased DNA integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 44 publications
8
112
1
Order By: Relevance
“…4), implying impaired sperm quality. Protamine deficiency in mature sperm from both mice and humans has been reported as a manifestation of DNA damage and fertility problems, as the protamine structure protects the genetic material from physical and chemical damage (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…4), implying impaired sperm quality. Protamine deficiency in mature sperm from both mice and humans has been reported as a manifestation of DNA damage and fertility problems, as the protamine structure protects the genetic material from physical and chemical damage (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Both protamines 1 and 2 are essential for sperm function, and the haploinsufficiency of either P1 or P2 results in a reduced amount of the respective protein, abnormalities in the structure of the chromatin, DNA damage and infertility [148]. Furthermore, it is known that the optimal protamine-1 to protamine-2 ratio (P1/P2 ratio) is critical and well regulated [166]. Indeed, the P1/P2 ratio in fertile men ranges from 0.8 to 1.2 and deviation from this ratio has been shown to lead to infertility [167].…”
Section: Epigenetic Modifications and Male Infertilitymentioning
confidence: 99%
“…These findings suggest that genetic sequence aberrations are an unlikely cause for protamine deficiency. Subsequent studies reported that patients with an elevated P1=P2 ratio under-expressed P2 protein and retained higher levels of protamine 2 transcript when compared to patients with normal or high P2 protein [Aoki et al 2006c;Torregrosa et al 2006]. However, patients with a diminished P1=P2 ratio under-expressed P1 protein and over-expressed P1 transcript [Aoki et al 2006c;Torregrosa et al 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reported that patients with an elevated P1=P2 ratio under-expressed P2 protein and retained higher levels of protamine 2 transcript when compared to patients with normal or high P2 protein [Aoki et al 2006c;Torregrosa et al 2006]. However, patients with a diminished P1=P2 ratio under-expressed P1 protein and over-expressed P1 transcript [Aoki et al 2006c;Torregrosa et al 2006]. Previous studies have indicated that patients with an elevated protamine 2 transcript had higher levels of DNA damage [Torregrosa et al 2006], whereas patients with increased protamine 1 transcript retention had low sperm motility [Lambard et al 2004;Aoki et al 2006c].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation